Funda????es de direito privado: influ??ncia dos fundadores na cultura organizacional - Paula, Mabel Bastos de (2011)
This dissertation objective is to study the founder influence in the organizational culture on private foundations. A qualitative survey was made, involving four independent nonprofit foundations, in Sao Paulo. Data about the participant organizations was collected through documentary research and semi structured interviews with the founders, CEOs and staff of each of them. Results showed that the influence of founders is mostly perceived when they are still involved in the organizations created by them, which bring their characteristics. In foundations where the founders are not present, their influence is perceived in the board of directors. Religious beliefs, and the foundation relation to religious or family groups are used to perpetuate founder values. The outcomes also show the role of staff on professional management of foundations. Managers in higher decision positions seem to have more influence in the organizational culture. They are able to propose organizational changes, when the mission defined on founding is flexible enough to allow modifications. Although it was not the aim of this study, some outcomes were found referred to more transparency and accountability in organizations that demand fundraising. Finally, some propositions and suggestions for future studies on founder influence and organizational culture are presented